Spinal accessory nerve transfer for shoulder abduction has no benefit over supraclavicular exploration and nerve grafting in brachial plexus birth injury: a systematic review - Mendiratta, Dhruv; Singh, Rohan; Abdelmalek, George; Pant, Krittika; Chu, Alice; McGrath, Aleksandra (Frontiers in Pediatrics, 2024)
Brachial plexus birth injury (BPBI) has an incidence of 0.9 per 1000 live births in the population. Techniques for repair classically include supraclavicular exploration and nerve grafting (SENG) and more recently nerve transfer, namely of the spinal accessory nerve (SAN) to the suprascapular nerve (SSN) to improve functional outcomes such as glenohumeral abduction and external rotation. This systematic review was conducted to evaluate whether spinal accessory nerve transfer produced significantly better outcomes for shoulder abduction in BPBI. A search was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analysis Individual Patient Data guidelines. Standardized comparisons were made using the Mallet Score for shoulder abduction. 10 full-text articles with itemized patient outcome measures were selected. 110 patients were identified with 51 patients in the SENG group and 59 patients in the SAN transfer group. The mean shoulder abduction Mallet score in the SENG group was 3.50±0.84, while the mean Mallet score in the SAN transfer group was 3.58±0.77, which displayed no significant differences (p=0.9012). There was no significant relationship between the age at time of surgery and post-operative Mallet scores for shoulder abduction after SENG (p=0.3720). Our systematic review found that there was no difference observed in post-operative outcomes of shoulder abduction when comparing SAN transfer and nerve grafting. Continued support for nerve grafting lies in the argument that it incorporates the patient's native neuroanatomy and allows for sensory reinnervation.